Impact on environmental assets: elucidating the Nutritional and immunological factors as the contributing to health status among flood victim in Kelantan - Hassan, Rosline (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2017)
Three-hundred and nine subjects were analyzed based on the result from materials and methods. The result showed the prevalence of household food insecurity among flood victim (n=71 ). Subject that categorized in food secure compromise of 28.4% while the rest were categorise as the food insecure groups (Household insecure (27.1%). Individual insecure (8.4%) and Child hunger (36.0%). In general. the food insecure household was characterized by household living under poverty line and had larger household size, more children, school going children and non-working. One-hundred fifty blood samples were analyzed with the age mean 47.0±15.62 (age range between 18-77yr) for male and 46.6±13.23 (age range between 19-87yr) for female. I. Based on the laboratory profiles, immunological status of the post flood victim were affected after the flood. Comparing to normal population, there were significant difference tor CD4% (p=0.015), CD8% (0.015) and CD4:CD8 ratio (p=0.012). II. Levels of lmmunoglobulin in female was higher as compared to control lgG (gll). p=0.000 and lgM (g/L). p=0.032. However no significant different shown in male immunoglobulin. Ill. In post flood victim. 1WBC and monocytes were higher among male (p<0.05) whereas only monocytes were higher in female (p<0.05).